2022
DOI: 10.3390/children9071070
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia—A New Diagnostic Marker for Complicated Acute Appendicitis in Children: A Systematic Review and Meta-Analysis

Abstract: Background: Acute appendicitis in the pediatric population remains a diagnostic challenge for clinicians. Despite many biochemical markers, imaging modalities and scoring systems, initial misdiagnosis and complication rates are high in children. This suggests the need for investigations directed towards new diagnostic tools to aid in the diagnosis. Recent studies have shown a correlation between serum sodium levels and complicated appendicitis. Although the exact reasons for hyponatremia in patients with compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The former being weak (r = – 0.28) and the latter, moderate (r = –0.46). Hyponatremia is a well-known alteration in complicated PAA, which agrees with our findings [ 18 ]. On the other hand, we expected the correlation between CK and creatinine to be positive.…”
Section: Discussionsupporting
confidence: 93%
“…The former being weak (r = – 0.28) and the latter, moderate (r = –0.46). Hyponatremia is a well-known alteration in complicated PAA, which agrees with our findings [ 18 ]. On the other hand, we expected the correlation between CK and creatinine to be positive.…”
Section: Discussionsupporting
confidence: 93%
“…For animals, it has been recognized that a certain concentration of extracellular sodium ions can resist the invasion of microorganisms. For example, in human body, the development of perforated appendicitis is related to the relatively low blood sodium [34][35][36][37]. It was also found that the seasonal low blood sodium of an American bat was related to its infection with a coronavirus and massive death [38,39].…”
Section: Out Of the Ideological Way Of Traditional Immunological Theo...mentioning
confidence: 99%
“…In addition to physical examination and image diagnosis, numerous laboratory markers such as white blood cells, neutrophil granulocytes, C-reactive protein, interleukins, sodium, bilirubin, red blood cell distribution width, mean platelet volume, etc. [4][5][6][7][8], as well as various scoring scales, help us to diagnose acute appendicitis [9][10][11]. Although acute appendicitis is the most common surgical abdominal pathology in children, it is still a challenge and diagnostic dilemma for pediatric surgeons despite all available diagnostic modalities.…”
Section: Introductionmentioning
confidence: 99%